1997
DOI: 10.1063/1.119760
|View full text |Cite
|
Sign up to set email alerts
|

Nitridation of silicon oxide layers by nitrogen plasma generated by low energy electron impact

Abstract: Low temperature nitridation of silicon oxide layers by nitrogen plasma generated by electron impact is investigated using x-ray photoelectron spectroscopy (XPS) and synchrotron radiation ultraviolet photoelectron spectroscopy and it is found that a large amount of nitrogen can be incorporated in the layers. The valence band structure of the oxide surface nitrided at 25 °C is similar to that of Si3N4, while that nitrided at 700 °C resembles the mixture of silicon oxide and silicon oxynitride. Measurements of XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The incorporation of nitrogen atoms at the surface/interface was commonly observed in the nitridation of SiO 2 because of the smaller activation energy at the surface/interface region. 30,32,33 We thus speculated that the N2 component resides at the dot/matrix interfaces rather than in the matrix.…”
Section: N-correlated Bonding Configuration At the Dot/matrix Intementioning
confidence: 97%
See 2 more Smart Citations
“…The incorporation of nitrogen atoms at the surface/interface was commonly observed in the nitridation of SiO 2 because of the smaller activation energy at the surface/interface region. 30,32,33 We thus speculated that the N2 component resides at the dot/matrix interfaces rather than in the matrix.…”
Section: N-correlated Bonding Configuration At the Dot/matrix Intementioning
confidence: 97%
“…In addition to an influence of the processing temperature, 32 the formation of the N2 component is specifically related to the interfacial region. 30,32,33 Kobayashi et al 32 reported that the processing temperature affects both the activities of ionic bonding and the stoichiometry of the SiO x N y matrix, which, in turn, alters the proportion of the N2 component. During our sputtering deposition, there was no significant substrate temperature variation; the increase of the N2 component with increasing dot size and density was thus not induced by thermal effects.…”
Section: N-correlated Bonding Configuration At the Dot/matrix Intementioning
confidence: 99%
See 1 more Smart Citation
“…The minor peaks for N3 and N4 can be attributed to nonstoichiometric silicon oxynitride and O 2 =N-Si formation, because the binding energy of the N 1s peak for SiN x species shifts their binding energy to a much higher level, depending on the x and nitrogen atoms that are bound to oxygen atoms. 11 The chemical states positioned at very high binding energy at 403.2 eV ͑N5͒ and 404.7 eV ͑N6͒, which can be assigned to molecular N 2 gas, are also observed in the Hf-silicate film during the nitridation process. The existence of two different chemical states caused by molecular N 2 gas can be explained by an extra-atomic relaxation effect, since the atomic relaxation effect can differently affect the N 2 molecule according to its surroundings.…”
mentioning
confidence: 93%
“…We have developed a low temperature formation method of SiON (or SiN) layers by use of nitrogen (N 2 )-plasma generated by the low energy electron impact method [22][23][24]. Using this method, SiON (or SiN) layers having a nitrogen atomic concentration more than 10% can easily be formed below 400°C.…”
Section: Introductionmentioning
confidence: 99%